2017
DOI: 10.1016/j.scitotenv.2016.12.142
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional oil and gas spills: Materials, volumes, and risks to surface waters in four states of the U.S.

Abstract: Extraction of oil and gas from unconventional sources, such as shale, has dramatically increased over the past ten years, raising the potential for spills or releases of chemicals, waste materials, and oil and gas. We analyzed spill data associated with unconventional wells from Colorado, New Mexico, North Dakota and Pennsylvania from 2005 to 2014, where we defined unconventional wells as horizontally drilled into an unconventional formation. We identified materials spilled by state and for each material we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…Spilled fluids included pit fluids, fuels, mud, fracturing fluid, chemicals, flowback, and brine. Synthesizing spill data from shale and tight gas wells in four U.S. states from 2005 to 2014, Maloney et al (2017) showed that spill rates were increasing in Colorado, New Mexico, and North Dakota over time, while Pennsylvania spill rates peak and decrease over time as discussed above. In the Niobrara Shale formation in northeastern Colorado, for example, the spill rate remained relatively constant from 2007 to 2011 at 1 spill recorded for every 100 wells, while from 2012 to 2014 the rate of spills doubled to 1 in 50 (Armstrong et al 2017).…”
Section: Mechanism Methods Of Quantificationmentioning
confidence: 87%
See 1 more Smart Citation
“…Spilled fluids included pit fluids, fuels, mud, fracturing fluid, chemicals, flowback, and brine. Synthesizing spill data from shale and tight gas wells in four U.S. states from 2005 to 2014, Maloney et al (2017) showed that spill rates were increasing in Colorado, New Mexico, and North Dakota over time, while Pennsylvania spill rates peak and decrease over time as discussed above. In the Niobrara Shale formation in northeastern Colorado, for example, the spill rate remained relatively constant from 2007 to 2011 at 1 spill recorded for every 100 wells, while from 2012 to 2014 the rate of spills doubled to 1 in 50 (Armstrong et al 2017).…”
Section: Mechanism Methods Of Quantificationmentioning
confidence: 87%
“…In the Niobrara Shale formation in northeastern Colorado, for example, the spill rate remained relatively constant from 2007 to 2011 at 1 spill recorded for every 100 wells, while from 2012 to 2014 the rate of spills doubled to 1 in 50 (Armstrong et al 2017). Synthesizing spill data from shale and tight gas wells in four U.S. states from 2005 to 2014, Maloney et al (2017) showed that spill rates were increasing in Colorado, New Mexico, and North Dakota over time, while Pennsylvania spill rates peak and decrease over time as discussed above. Spill rates were between 2 and 16 per 100 new wells, up to 47% of which were located within each state's respective stream setback limits, suggesting possible surface water contamination.…”
Section: Methods Of Quantificationmentioning
confidence: 99%
“…However, the large increase in proximity to access roads and well pads is still likely to have impacts on the ecological functioning of prairie potholes. This type of development is likely to cause increases in run-off and sedimentation (Entrekin, Evans-White, Johnson, & Hagenbuch, 2011;Post van der Burg & Tangen, 2015), chemical pollution (from wells, vehicles, and winter road treatments; Amrhein, Strong, & Mosher, 1992;Coffin, 2007;Drapper, Tomlinson, & Williams, 2000;Green, Machin, & Cresser, 2008;Maloney et al, 2017), noise pollution (Kight & Swaddle, 2011), light pollution (Longcore & Rich, 2004), direct animal mortality from traffic (Fahrig & Rytwinski, 2009;Sargeant, 1981), and dust (Farmer, 1993). Even if well pad and road development remains distant enough to have minimal direct impacts on wildlife, animals often exhibit behavioral changes to decreasing development distances (Kociolek, Clevenger, St Clair, & Proppe, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hazards and risks associated with owback and produced water include hazards associated with accidental spills, leaks, and other emissions. [8][9][10][11] Concerns also arise from the potential contamination of surface water and aquifers due to poor well construction or maintenance, disposal of spent uids, and disposal of uids generated during oil and gas production. 7, 12,13 Previous studies have investigated the phenomenon of owback in produced water from stimulated wells and found that water quality of the return-ow changed over time, typically with an initial composition (as indicated by total dissolved solids (TDS) or other chemical indicators) similar to the injected uid, with a gradual transition to more saline connate water.…”
Section: Introductionmentioning
confidence: 99%